"you can't be deterred by stuff you don't know about": Identifying factors that influence graduated driver licensing rule compliance. (January 2019) - Truelove, V.; Freeman, J.; Davey, J.
Highlights: Phone related Graduated Driver Licensing (GDL) restrictions were widely unknown. Perceptions of GDL enforcement were connected to displaying provisional licence plates. GDL phone restriction and passenger phone restriction were complied with least. GDL alcohol restriction was the most complied with restriction. Compliance linked with certainty, severity, social acceptance, legitimacy, safety. Abstract: This study aimed to identify and explore the major mechanisms that influence young drivers' compliance with the Queensland, Australia Graduated Driver Licensing (GDL) (also known as graduated licensing or graduated driver licensing systems) restrictions. Due to the limited research focus on compliance with GDL restrictions, a qualitative approach was utilised. The study consisted of 11 focus groups ( N  = 60) of young Queensland drivers aged between 17 and 25 years ( M age = 20.50 years, SD  = 2.69). Results were analysed using an inductive thematic analysis. Participants had low perceptions of enforcement certainty for the GDL restrictions, due to the difficulty in identifying these behaviours. Enforcement of these restrictions is linked to displaying the provisional licence (P) (also known as intermediate licence) plates, however this was reported to be violated quite often. Surprisingly, a number of the restrictions were unknown to participants, despite the restrictions being in place for over 10 years. The GDL phone restriction, particularly using the phone for Global Positioning Service (GPS) applications and the use of Bluetooth to listen to music, as well as the passenger loudspeaker restriction were the least complied with restrictions. Meanwhile, the zero-alcohol limit was the most complied with restriction. Compliance with these restrictions was linked with perceptions of enforcement certainty and severity, social acceptance, as well as perceptions of legitimacy of the restriction and perceived danger associated with violating the restriction. The punishments for violating these restrictions were widely unknown and several participants stated they were more likely to comply with the restrictions when they found out the severity of the punishments. This study identified differences in compliance with each GDL restriction, as well as detecting a number of factors that influence compliance. These results can aid in the development of countermeasures that may improve GDL rule compliance, and the young driver road trauma rate.